Creativity, Thought and Feminist Artivism in Chile: Now is when! - Freire Smith, Marla (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2020)
The actions made by feminist colectives and groups in Chile has reconfigured the ways of conceiving action art and generates collective catharsis. “Acuerpar” the public space, renaming Metro de Santiago stations and streets to make women visible, show historical omission but also epistemic violence. Based on feminist epistemologies, this article analizes how creativity and feminisms through performativity expressed by different groups and artists (Yeguada Latinoamericana y LasTesis, among others), power structures can be destabilized and deconstruct the history(s).